Pueraria protein extract inhibits melanogenesis and promotes melanoma cell apoptosis through the regulation of MITF and mitochondrial‑related pathways - Zhao, Yuchu; Yu, Shiting; Wang, Yue; Chen, Yanyan; Chen, Jingjing; Wang, Jiawen; Liu, Meichen; Wang, Siming (Molecular medicine reports, 2023)
Radix ( Radix) is an edible traditional Chinese medicine that contains various active compounds. Proteins from Radix have become the subject of increased interest in recent years. In evaluating the whitening effect on the skin, the present study found that the Radix water‑soluble total protein extract (PLP) had the strongest inhibitory effect on tyrosinase activity. In the present study, the anti‑melanogenic effect of PLP and the inhibitory effect on B16 melanoma cells were investigated. PLP significantly reduced the tyrosinase activity and melanin content in B16 melanoma cells. Mechanistically, PLP inhibited melanogenesis by decreasing the expression of tyrosinase, tyrosinase‑related protein (TRP)‑1 and TRP‑2 through downregulation of the microphthalmia‑associated transcription factor (MITF) gene, which was mediated by inhibition of p38 mitogen‑activated protein kinase signaling. In addition, PLP inhibited cell viability and triggered apoptosis of B16 cells in a dose‑dependent manner. Exposure to PLP reduced the mitochondrial membrane potential (MMP) and decreased ATP generation, leading to mitochondria‑related apoptosis of B16 melanoma cells. The expression levels of succinate dehydrogenase (SDH) and its two related subunits (SDHA and SDHB) were downregulated significantly by PLP, which may be associated with the regulation of mitochondrial energy metabolism by PLP. These results may explain why MMP collapse and reduced ATP generation were observed in B16 melanoma cells treated with PLP. Finally, the present study demonstrated that the inhibition of melanin synthesis by PLP was correlated with the regulation of antioxidant enzymes to reduce reactive oxygen species levels. These results suggested that PLP inhibits melanogenesis by downregulating the expression of MITF‑related melanogenic enzymes and triggering apoptosis through mitochondria‑related pathways.